2014
DOI: 10.1088/0953-8984/26/18/185901
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition of the uniaxial disordered ferroelectric Sr0.61Ba0.39Nb2O6

Abstract: Abstract. We report a neutron scattering study of a ferroelectric phase transition in Sr 0.61 Ba 0.39 Nb 2 O 6 (SBN-61).The ferroelectric polarization is along the crystallographic c-axis but the transverse acoustic branch propagating along the <1, 1, 0> direction does not show any anomaly associated with the this transition. We find no evidence for a soft transverse optic phonon. We do, however, observe elastic diffuse scattering. The intensity of this scattering increases as the sample is cooled from a tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…At the same time, the Lorentzian profile of the OPF diffuse scattering component within the a à b à reciprocal plane has been thoroughly studied in the past and its 5-10 unit cell transverse correlation length is well established [51][52][53]. Therefore, the present results allow us to combine the information about temporal and spatial correlations associated with Vogel-Fulcher-type dielectric relaxations of SBN61.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…At the same time, the Lorentzian profile of the OPF diffuse scattering component within the a à b à reciprocal plane has been thoroughly studied in the past and its 5-10 unit cell transverse correlation length is well established [51][52][53]. Therefore, the present results allow us to combine the information about temporal and spatial correlations associated with Vogel-Fulcher-type dielectric relaxations of SBN61.…”
mentioning
confidence: 70%
“…It was found that the intensity profile of the narrower component, monotonically increasing with decreasing temperature, can be well described by a simple model for scattering by domain walls and that its presence can be effectively suppressed by a bias electric field of a few kV=cm [51,53,54]. On the other hand, the intensity of the broader component has a temperature dependence similar to the dielectric permittivity with a maximum near T max and the electric field has a much smaller influence here.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…There is a strong change in polarization aging under light illumination in SBN-61:Ce [14]. Thus, the macroscopic properties of doped SBN-61 crystals have much in common with relaxors.The phase transition of pure SBN-61 has been recently studied by neutron scattering [15][16][17]. On approaching from above the transition temperature, T C , a slow dynamic diffuse scattering (DS) emerges in the neutron spectra [16,17].…”
mentioning
confidence: 99%